Implementasi Profile Matching Pada Seleksi Ketua dan Wakil Ketua OSIS - Alif Iftitah; Linda Perdana Wanti; Dwi Novia Prasetyanti; Nur Wachid Adi Prasetya; Andriansyah Zakaria (P3M Politeknik Negeri Cilacap, 2022)
The OSIS chairman is the highest leader in the OSIS management structure and is accompanied by a vice-chairman. Therefore, a selection with several criteria is needed to determine the best candidate. Things that are considered in this selection are realism, maturity, organizational experience, public speaking, discipline, character, organizational activity, and responsibility. By utilizing a decision support system, the best candidates are obtained for the candidate for chairman and vice-chairman of the student council. This system is made with the method used to assist the selection process, namely, profile matching. Profile matching is used to find the profile of a job that is sought from a predetermined specification. This method provides a solution and has a clear objective in decision-making. On the other hand, the method used to develop a decision support system is the incremental method. The selection of the incremental method is based on the fact that this method has an iterative nature, which can adapt to the many repetitions that occur during the development process. The novelty of this research is the recommendations generated from the developed decision support system. There are notifications about the results of decisions to users, in this case, the candidates for the OSIS chairman and vice chairman who are alternatives in the election process. This study resulted in recommendations in the form of candidates for OSIS chairman and vice chairman by the candidate's profile.